2011
DOI: 10.1007/s00425-011-1434-8
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping of dynamic developmental plant height in common wheat

Abstract: Drought as a major abiotic stress often occurs from stem elongation to the grain filling stage of wheat in northern China. Plant height (PH) is a suitable trait to model the dissection of drought tolerance. The purposes of the present study were to validate molecular markers for PH developmental behavior and identify elite alleles of molecular markers. After the phenotyping of 154 accessions for PH dynamic development under well-watered (WW) and drought stressed (DS) conditions, and the genotyping of 60 SSR ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 35 publications
(54 reference statements)
1
31
0
Order By: Relevance
“…A limited water supply often inhibits plant height development. As it is very easily measured and remains constant after flowering, PH usually serves as a suitable agronomic trait for evaluating drought tolerance in crop plants [29,30]. In addition, seedling biomass is an effective criterion for identifying drought tolerance in plants [31,32], and other traits, such as flag leaf width and water-soluble carbohydrates, were proposed as key traits supporting grain yield under stress conditions in wheat [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A limited water supply often inhibits plant height development. As it is very easily measured and remains constant after flowering, PH usually serves as a suitable agronomic trait for evaluating drought tolerance in crop plants [29,30]. In addition, seedling biomass is an effective criterion for identifying drought tolerance in plants [31,32], and other traits, such as flag leaf width and water-soluble carbohydrates, were proposed as key traits supporting grain yield under stress conditions in wheat [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al [44] found that allele Xgwm130 132 underwent very strong positive selection for 1,000 kernel weight during modern breeding. Through association mapping of dynamic development of plant height in common wheat, Zhang et al [53] exposed different allelic effects of associated markers; gwm495-4B 155 was associated with reduced height of −11.2 cm under drought stressed and −15.3 cm under well watered conditions, whereas the 167 bp allele exhibited increased height effects of 3.9 and 8.1 cm, respectively. In the present study, different allelic effects of significant loci were also found for FHB response (Figure 4, Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…However, current gene mapping efforts in plants are shifting from conventional biparental QTL mapping to LD-based association mapping (Sorkheh et al 2008), which is the most effective approach to utilize natural variation in the form of ex situ conserved crop genetic resources. Some successful reports on association mapping in plants such as rice (Yan et al 2009), barley (Kraakman et al 2006), wheat (Ghavami et al 2011;Zhang et al 2011Zhang et al ), potato (D'hoop et al 2008, soybean (Jun et al 2007), maize (Andersen et al 2007), chickpea (Saeed et al 2013), and forage grasses (Dobrowolski & Forster 2007) are available. To our knowledge, this is the first report on the identification of responsible locus for chloride accumulation rate via association mapping in tobacco.…”
Section: Qtl Mappingmentioning
confidence: 99%